2009
DOI: 10.1007/s00606-009-0208-2
|View full text |Cite
|
Sign up to set email alerts
|

What phylogeny and gene genealogy analyses reveal about homoplasy in citrus microsatellite alleles

Abstract: Sixty-five microsatellite alleles amplified from ancestral citrus accessions classified in three separate genera were evaluated for sequence polymorphism to establish the basis of inter-and intra-allelic genetic variation, evaluate the extent of size homoplasy, and determine an appropriate model (stepwise or infinite allele) for analysis of citrus microsatellite alleles. Sequences for each locus were aligned and subsequently used to determine relationships between alleles of different taxa via parsimony. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 46 publications
2
44
0
4
Order By: Relevance
“…A basic assumption of the MAC-PR method is the repeatability of relative allelic amplification intensities among individuals and, thus, the total homology of primer sites for DNA fragments producing the same allele (same PCR product size). Homoplasy of SSR markers was found at interspecific levels in citrus (Barkley et al, 2009), and could limit general application of MAC-PR. 'Fortune' mandarin and most of the male genitors used in our study are closely related, which should explain why we have not encountered this difficulty because of the by-descent homology of alleles.…”
Section: Discussionmentioning
confidence: 99%
“…A basic assumption of the MAC-PR method is the repeatability of relative allelic amplification intensities among individuals and, thus, the total homology of primer sites for DNA fragments producing the same allele (same PCR product size). Homoplasy of SSR markers was found at interspecific levels in citrus (Barkley et al, 2009), and could limit general application of MAC-PR. 'Fortune' mandarin and most of the male genitors used in our study are closely related, which should explain why we have not encountered this difficulty because of the by-descent homology of alleles.…”
Section: Discussionmentioning
confidence: 99%
“…While microsatellites were developed initially for mapping and population genetic studies, Ochieng et al (2007b) found them helpful for phylogenetic resolution of eucalypt genera. Microsatellite loci are selected by researchers to be highly polymorphic within species and their use for taxonomic purposes between closely related species is limited by the unreliable transferability of these markers across species boundaries (e.g., see Nevill et al 2008) and by the risk of high levels of homoplasy that might be encountered (e.g., Barkley et al 2009;Curtu et al 2004). Hence, while microsatellites have the potential to provide phylogenetic resolution at high taxonomic levels (between genera) and are very useful for population-level studies within species, they are impractical for phylogenetic reconstruction between taxonomic extremes.…”
Section: Introductionmentioning
confidence: 99%
“…Methods such as restriction fragment length polymorphism (Fang et al, 1997;Fu et al, 2004), randomly amplified polymorphic DNA (AkaKacar et al, 2005;Rodriguez et al, 2005), amplified fragment length polymorphism (Fu et al, 2004;Campos et al, 2005), simple sequence repeats (SSR) (Barkley et al, 2006(Barkley et al, , 2009, inter-simple sequence repeats Capparelli et al, 2004), and sequence-related amplified polymorphism (SRAP) (Uzun et al, 2009) have been used.…”
Section: Introductionmentioning
confidence: 99%
“…SSR markers have been the most commonly implemented markers in molecular biology for mapping, genetic diversity, phylogenetic construction, and fingerprinting because they are codominant, highly polymorphic, and easy to use (Barkley et al, 2009). SRAP markers are part of a simple and efficient system that can be adapted for a variety of purposes in various crops, including map construction, gene tagging, genomic and complementary DNA fingerprinting, and map-based cloning (Li and Quiros, 2001;Comlekcioglu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%